Dilema Pengawasan Partisipatif: Ikatan Patrimonial dan Masyarakat yang Terkooptasi di Jawa Timur - Andy Ilman Hakim; Deydeandy L. Iztighfari (Jurnal Adhyasta Pemilu, 2019)
The concept of participatory oversight focuses on people’s involvement in election monitoring. This means that the people are not only built on awareness to exercise their right to vote, but also to be actively involved in the entire election process. The implementation of participatory oversight has been running and implemented since the 2009 elections. However, there are still various problems, especially in East Java Province. The number of people in East Java who use voting rights is very high, but the data shows that East Java is the province with the highest of election violations and people’s involvement in reporting violations is very weak. This research uses a qualitative approach to analyze the problem of people’s involvement in election monitoring. The research findings show the three important aspects that cause low people’s involvement in the election monitoring process in East Java. First, there is no work innovation from Bawaslu at regional level. Second, patrimonial society. Third, found the practice of money politics and intimidation to the people by the political elite hurts society. The negative impact creates the problem of election monitoring by the public in East Java, as an impact of co-opted communities.